CPD article: Biofilms and surgical site infections. (2nd March 2022) - Low, Daniel; Aldridge, Paul
Abstract : Surgical site infections are common in small animal veterinary practice, and can result in increased morbidity and mortality as well as adding to overall healthcare costs. Surgical site infections are nosocomial infections and can be classified as superficial incisional, deep incisional, or organ-space. Biofilm-producing bacteria in surgical site infections have survival advantages compared to sessile bacteria, making diagnosis and treatment more challenging. Treatment of surgical site infections varies and depends on the type of infection, drug susceptibility, patient factors and wound factors. Preoperative, intraoperative, and postoperative measures can be taken to prevent the development of surgical site infections. Surgical materials to reduce the likelihood of biofilm formation have been developed, but strong evidence to support their use is lacking. Further prospective veterinary studies and the development of active veterinary surveillance programmes are warranted.